Guidelines from the Canadian Association of Pathologists for establishing a telepathology service for anatomic pathology using whole-slide imaging - Chantal Bernard; S A Chandrakanth; Ian Scott Cornell; James Dalton; Andrew Evans; Bertha M Garcia; Chris Godin; Marek Godlewski; Gerard H Jansen; Amin Kabani; Said Louahlia; Lisa Manning; et al. (Elsevier, 2014)
The use of telepathology for clinical applications in Canada has steadily become more attractive over the last 10 years, driven largely by its potential to provide rapid pathology consulting services throughout the country regardless of the location of a particular institution. Based on this trend, the president of the Canadian Association of Pathologists asked a working group consisting of pathologists, technologists, and healthcare administrators from across Canada to oversee the development of guidelines to provide Canadian pathologists with basic information on how to implement and use this technology. The guidelines were systematically developed, based on available medical literature and the clinical experience of early adopters of telepathology in Canada. While there are many different modalities and applications of telepathology, this document focuses specifically on whole-slide imaging as applied to intraoperative pathology consultation (frozen section), primary diagnosis, expert or second opinions and quality assurance activities. Applications such as hematopathology, microbiology, tumour boards, education, research and technical and/or standard-related issues are not covered.